Reference groups and the poverty line: An axiomatic approach with an empirical illustration - Satya R. Chakravarty; Nachiketa Chattopadhyay; Zoya Nissanov; Jacques Silber (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
A recent trend in the study of poverty is to consider a relative poverty line, one that is responsive to the nature of the income distribution. We develop an axiomatic approach to the determination of an amalgam poverty line. Given a reference income (e.g. the mean or the median), the amalgam poverty line becomes a weighted average of the absolute poverty line and the reference income, where the weights depend on the policy maker's preferences for aggregating the two components. The paper ends with an empirical illustration comparing rural and urban and areas in the People's Republic of China and India.
Keywords: D31; D63; I32; 330; absolute poverty; amalgam threshold; India; People's Republic of China; poverty line; relative poverty